The significance of radiological methods in the diagnostics of Gastroenterological diseases (according to the materials of the 18th Russian Gastroenterology Week) - Z. A. Lemeshko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of the Review. To analyze the publications and the reports devoted to the radiological methods in the diagnostics of the gastroenterological diseases and present to gastroenterologists and other physicians the state-of-the art possibilities of these methods.Key points. The findings of the research studies and practical use of the radiological methods in the diagnostics of the diseases of the liver, biliary tract, pancreas, gastrointestinal tract, spleen, etc. were presented. The increase in the demands to the imaging studies and the enlarging of the sphere of the questions to be addressed in this regard were marked.Conclusion. In the recent years the radiological methods are used not only in the detection of the different morbid conditions but in the differential diagnostics of the digestive diseases both in the therapeutic practice as well as during the small invasive interventions. They play the important role in the follow-up of the course of the pathological processes.